Examining BMT's Role in Boosting Member Income: A Case Study in Kamang Mudiak - Ady Bakri, Asri (Takaza Innovatix Labs Ltd., 2023)
The background of this research is motivated by the presence of members who need funds to run their business in Kamang Mudiak and the amount of per capita income of the community or residents that has remained relatively high. At the same time, this research aims to increase people’s income. Type of research used in the form of field research that is descriptive qualitative. The technique of collating data through interviews with informants (BMT employees and some people from the community), observation, and documentation. The data analysis technique uses analysis techniques, according to Miles and Huberman, which consists of data collection, data processing, data presentation, and conclusion. The results of this study indicate that the presence of BMT in Nagari Kamang Mudiak has been effective in helping people’s income. This can be seen from the distribution of additional capital distributed by BMT to the community. From this capital, the community manages it well so that they can develop their businesses to be more productive and more advanced and to improve their economy even better.